Comprehensive Analysis Of Ranitidine Usage: Pharmacological Interactions, Safety In Polypharmacy And Effects On Disease Management - CU, Mufeedha; Ravi, Krishna; Simon, Alwin (Journal of Neonatal Surgery, 2025)
Background: The selective histamine type 2 receptor antagonists/blockers (H2 blockers) are widely used in the treatment of acid-peptic disease, including duodenal and gastric ulcers, gastroesophageal reflux disease, and common heartburn. Aim And Objectives: To comprehensively evaluate the indications, pharmacological interactions, and safety profile of ranitidine in polypharmacy prescriptions within the general medicine department. Methodology:The six-month observational cross-sectional study was conducted in a tertiary care teaching hospital. Informed consent was collected from all the participants. All the patients (363) were monitored for drug interactions and adverse drug reactions. Results And Discussion: Results showed that in this study, 54.2% of participants used ranitidine for non-labeled indications, exceeding the 45.7% who used it for approved purposes. Out of 363 study participants, 45.7% (166) were prescribed ranitidine for labeled indications (such as GI ulcers and GERD), aligning with approved uses for acid suppression. Rashes are the most frequent ADR, affecting 50.6% of patients, indicating a notable dermatological impact. Bradyarrhythmia, observed in 38.51% of cases, underscores the need for vigilant cardiac monitoring due to its serious nature. Out of 363, 204(56.19%) prescriptions are inappropriate polypharmacy, and among these, deprescribing is done in 56 prescriptions, and dose adjustment made in 20 prescriptions. Conclusion: The comprehensive analysis of ranitidine usage reveals a high prevalence of conditions that may be affected by ranitidine therapy due to inappropriate use. This study highlights the importance of closely monitoring pharmacological interactions in polypharmacy, especially when using ranitidine among patients with complex health profiles.